Increase thermal comfort by integrating ELT at building foundation: an alternative recycling way in Malaysia - Eusuf, Muhammad Abu; Hasan , Abdullah Al (IISTE, 2015)
Today, when people think of the environmental impacts of ELTs (end-of-life tyres), they mostly focus on the management of tyres at the end of their useful lives. Globally, an estimated one billion tyres reach the end of their useful lives every year. It is observed from literature that about 4 billion ELTs are currently in landfills and stockpiles worldwide and are disposed to unknown and illegal routes. It is also revealed that most of the countries currently are not experienced with the disposal of ELT with the framing of specific law or regulation to the disposal of ELT management. Hence ELT created a massive waste in management system which intern modified our environment. Recently it is obvious that should find out alternative ways as to reduce the massive ELT waste.This study has been designed to manage ELTs massive waste by experiment. In that reason we needed to set up an experimental set up to observe the real phenomena of ELT for passive cooling in hot humid and tropical climate and that compare with conventional construction materials and systems. Experimental setup foundations are constructed by using ELTs and other conventional foundation materials at IIUM (Gombak) campus. This paper presents the results, analysis and recommendations from the experimental tests and outputs.